2006
DOI: 10.1111/j.1467-629x.2006.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Success of activity management practices: the influence of organizational and cultural factors

Abstract: This study examines the success of activity management practices and the organizational and cultural factors affecting success at each of Gosselin's (1997) three levels of activity analysis (AA), activity cost analysis (ACA) and activity-based costing (ABC). Data were collected by survey questionnaire from a random sample of managers of Australian business units. The results indicate that activity management is moderately successful in Australian organizations, with greater use associated with higher levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 16 publications
5
99
2
6
Order By: Relevance
“…Top management support is also directly associated with local management involvement that is seen as important is garnering local union support (Anderson and Young, 1999). Baird et al (2007) examining three different levels of activity management adoption found that top management support was crucial to all levels according to their financial controller respondents.…”
Section: Top Management Supportmentioning
confidence: 99%
“…Top management support is also directly associated with local management involvement that is seen as important is garnering local union support (Anderson and Young, 1999). Baird et al (2007) examining three different levels of activity management adoption found that top management support was crucial to all levels according to their financial controller respondents.…”
Section: Top Management Supportmentioning
confidence: 99%
“…If businesses integrate ABC systems with quality initiatives, such as TQM, just-in-time and other speed initiatives, the success of ABC is more likely. This is similar to Shields (1995), Krumwiede (1998), andBaird et al (2007) who stated that LIQs are important for management tools, such as the ABC system. If ABC information supports quality initiatives, the usefulness of ABC will be clear and therefore it will contribute to ABC success.…”
Section: Discussionmentioning
confidence: 53%
“…Shields (1995), Baird et al (2007), and Chongruksut and Brooks (2005) stated that ADEs encompass the time and commitment of management, accountants, and operating employees. In addition, Majid and Sulaiman (2008) argued that personal education, specifically in the use of ABC software, external consultants, and training should be considered.…”
mentioning
confidence: 99%
“…The above examination shows that ABC is the most talked about techniques introduced to practitioners in Australia. This is in line with the suggestions made by studies which examined the implementation of ABC in practice (Al-Omiri & Drury, 2007a;Alcouffe, Berland, & Levant, 2008;Alsaeed, 2005;Baird et al, 2007;Englund & Gerdin, 2008;Kallunki & Silvola, 2008;Major & Hopper, 2005). However, as Table 1 shows, there are a variety of other management accounting practices which have been addressed in the literature and introduced to Australian practitioners through professional journals, workshops and conferences in recent years.…”
Section: The Extent Of Introduction Of Recently Developed Cost and Mamentioning
confidence: 66%
“…could influence the diffusion of innovations in organizations (Adam & Fred, 2008;Al-Omiri & Drury, 2007a;Askarany, 2006;Askarany & Smith, 2004Berling, 2008;Englund & Gerdin, 2008;Qian & Ben-Arieh, 2008;Yazdifar, Askarany, Askary, & Daneshfar, 2005). However, while the majority of studies initiated by the above theories and metaphors and found some associations between management accounting changes and some contextual factors (addressed by adopted theories), the findings are inconclusive, inconsistent, and mixed (Al-Omiri & Drury, 2007a;Baird, 2007;Baird, Harrison, & Reeve, 2007;Cobb, Innes, & Mitchell, 1993;Innes & Mitchell, 1995;Innes, Mitchell, & Sinclair, 2000;Langfield-Smith, 1997;Pierce, 2004;. Furthermore, from organizations' point of views, understanding factors contributing to innovative behavior in organizations and influencing organizations' decisions to proceed with the changes have remained relatively undeveloped, inconclusive, and inconsistent (Cho & Pucik, 2005).…”
Section: Introductionmentioning
confidence: 94%